UZBEKISTAN’S EXPERIENCE IN PREVENTING CORRUPTION BASED ON PUBLIC CONTROL. - Latipov Sardor Shavkatovich (TADQIQOTLAR.UZ, 2024)
Annotation: This article deals with the implementation of the policy of openness in the prevention of corruption, the rule of law by state bodies, the role of the public and mass media, honesty and impartiality.